Available Evidence and Ongoing Clinical Trials of Remdesivir: Could It Be a Promising Therapeutic Option for COVID-19? - Sisay, Mekonnen (Frontiers in Pharmacology, 2020)
The novel coronavirus strain, SARS-CoV-2, the causative agent of COVID-19 emerged in Wuhan, China, in December 2019 and has rapidly spread throughout the world and infecting nearly a million people. World Health Organization (WHO) has recommended routine laboratory tests for any suspected cases alongside quarantining suspects, applying social distancing and frequent handwashing to contain the spread of 2019-nCoV. Despite such preventive strategies, there is no recommended drug therapy officially approved by Food and Drug Administration (FDA) for COVID-19 until the time of this review. At present, there are several classes of drugs undergoing clinical trials. This review is specifically aimed to summarize the available evidence and ongoing clinical trials of remdesivir as a potential therapeutic option for COVID-19. Remdesivir is an investigational drug having broad spectrum antiviral activity with its target RNA dependent RNA polymerase. It has not been officially approved by FDA for Ebola and Coronaviruses. Several studies showed that remdesivir had a promising in vitro and in vivo antiviral activities against SARS-CoV-1 and MERS-CoV strains. On the top of this, it exhibited a promising in vitro activity against SARS-CoV-2 strains though there are no studies that substantiate its activity in vivo until the time of this review. Three are three randomized double-blind placebo controlled trials (two phase 3 and one phase 2) on the way to investigate the safety and efficacy of remdesivir. Another two phase 3 randomized open label clinical trials coordinated by Gilead Sciences are being conducted.